2018
DOI: 10.1177/1179552217746645
|View full text |Cite
|
Sign up to set email alerts
|

The Morbidity and Mortality of Laparoscopic Appendectomy in Patients with Cirrhosis

Abstract: Introduction:The perioperative mortality is significantly higher in patients with cirrhosis undergoing certain surgical procedures. In this study, we examined the inpatient perioperative mortality and morbidities in cirrhotic people who underwent laparoscopic appendectomy.Methods:We performed a retrospective analysis using the National Inpatient Sample database for 2010. Inclusion criteria were all race and sex who are 18 years or older. Those who have laparoscopic appendectomy and have a history of liver cirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
12
2
1
Order By: Relevance
“…2 However, in our study, because of the longer HLOS in DC patients treated by OA, the total cost of LA was markedly lower. Of interest, our HLOS was much shorter than Tsugawa et al 2 but much longer than reported by Al-Azzawi et al, 5 which cites 1.1 and 1.52 days for NC and cirrhotics, respectively, from the 2010 NIS data. We are unaware of what could have caused the significantly longer stays nationwide a few years later.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…2 However, in our study, because of the longer HLOS in DC patients treated by OA, the total cost of LA was markedly lower. Of interest, our HLOS was much shorter than Tsugawa et al 2 but much longer than reported by Al-Azzawi et al, 5 which cites 1.1 and 1.52 days for NC and cirrhotics, respectively, from the 2010 NIS data. We are unaware of what could have caused the significantly longer stays nationwide a few years later.…”
Section: Discussioncontrasting
confidence: 53%
“…The best management option for AA in cirrhotic patients is controversial, and it has not yet been established by high-powered prospective research. Compared with the available publications, 2,3,5 this study analyzed the largest number of cirrhotics with AA (n 4 438) and, for the first time, stratified patients based on the severity of cirrhosis. Not surprisingly, cirrhotics fared worse in all primary outcome measures compared with NC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies span an 18-year period from 2001 to 2019. Two studies were undertaken in the USA [ 17 , 29 ], one in Denmark [ 16 ], and one in Japan [ 28 ]. Three were nationwide database studies [ 16 , 17 , 29 ], and one, a retrospective observational study undertaken at two centres [ 28 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, most data regarding appendicitis derives from retrospective cohort studies, with conflicting rates of complications and mortality. For example, a Danish nationwide database study found an eight-fold increase in mortality in patients with cirrhosis [ 16 ] whereas a USA nationwide database study found no difference [ 17 ]. Consequently, decision-making in daily practice remains unclear.…”
Section: Introductionmentioning
confidence: 99%